Learning in the countryside: pen, hoe and the peasant botany - Matias Köhler; Estela Santos; Cristiane Giaretta; Gilmar Gomes; Sebastião Pinheiro (Universidade Federal do Norte do Tocantins, 2018)
In this paper, we present and discuss experiences of the execution of the project "Exchange of Knowledge on Peasant Botany", carried out during 2014 at the Assentamento Filhos de Sepé (Viamão, RS) with the group "Mulheres da Terra" and the Technological Incubator of Popular Cooperatives. An important characteristic of the Group is the role of women. Maintainers of knowledge and ancestral practices. They become active in all spheres of agriculture production of the settlement. Throughout 12 meetings, several themes related with agroecological practices with peasant life were addressed using different approaches: theoretical, practical and reflexive. Based on educational assumptions that value popular knowledge, as well as the horizontality of teaching/learning processes, the meetings contributed to the recognition and strengthening of the group's identity of resistance against the current globalized agriculture. Likewise, the progress was made in the construction of autonomy in the face of techniques and knowledge applied to agroecological production.